A PUZZLING CASE OF SEVERE PULMONARY HYPERTENSION - A CASE REPORT - Arif, Muhammad Sohaib; Ammar, Ali; Tauseef, Usman; Shaikh, Abdul Hakeem; Shaikh, Abdul Sattar; Abubaker, Jawed (Journal of Ayub Medical College Abbottabad, 2025)
Pulmonary hypertension (PH) is a life-threatening cardiopulmonary disorder marked by elevated pressure in the pulmonary arteries. We report a 51-year-old male, post-pericardectomy, presenting with breathlessness. Diagnosis revealed pulmonary hypertension with depressed right ventricle function. Managed with non-invasive ventilation (NIV) and oxygen, he was slated for right heart angiography but couldn't lie flat. Fluoroscopy identified bilateral diaphragm paralysis. Due to a lack of diaphragm-related procedures, he continued non-invasive ventilation, oxygen, and pulmonary vasodilators. With these measures, the functional status of the patient improved and he was able to carry out his routine activities.